Evaluating Anatomy Education in Kastamonu Çatalzeytin Vocational Higher Schools through Student Feedbacks - Şahin Öztürkcan, Derya; Harmandaoğlu, Oğuzhan; Ünver Doğan, Nadire (Selcuk University, 2024)
Aims: The aim of this study is to assess the attitudes of students in Vocational Higher Schools by obtaining their opinions, regarding the Anatomy course. Methods: This study is a survey-based research aimed at evaluating the opinions of 639 students enrolled in different programs (Disability Care and Rehabilitation, Physiotherapy, and Elderly Care Programs) at Kastamonu University Çatalzeytin Vocational Higher School regarding the Anatomy course, which they have taken theoretically. The survey questionnaire consists of 29 questions related to the evaluation of theoretical classes and eight questions related to the evaluation of exams. The survey questions were created online, and the participating students were provided with a link to access the survey questionnaire. Results: When asked about the contribution of the Anatomy course content to their professional development, 60.5% of the students responded positively, while 18.2% responded negatively. In regards to the inclusion of practical classes alongside theoretical classes, 80.9% of the students responded positively, while 7.1% responded negatively. Regarding the evaluation of exams, 63.8% of the students responded positively to the question of including visual-based questions in theoretical exams, while 19.5% responded negatively. When asked about the inclusion of practical exams alongside theoretical exams, 50% responded positively, while 27.6% responded negatively. Conclusions: Based on the findings of this study, which incorporates the opinions of the students, it is emphasized that practical classes should be included alongside theoretical classes in Anatomy education. Furthermore, it is noted that reminder sessions would be beneficial in the following years due to the tendency of forgetting the content of the Anatomy course.